Enhancing virtual environment-based surgical teamwork training with non-verbal communication - Marks, S; Windsor, J; Wünsche, B (INSTICC Press 2009, 2009)
Virtual reality simulations for training surgical skills are increasingly used in medical education and have been shown to improve patient outcome. While advances in hardware and simulation techniques have resulted in many commercial applications for training technical skills, most of these simulators are extremely expensive and do not consider non-technical skills like teamwork and communication. This is a major drawback since recent research suggests that a large percentage of mistakes in clinical settings are due to communication problems. In addition, training teamwork can also improve the efficiency of a surgical team and as such reduce costs and workload. We present an inexpensive camera-based system for capturing aspects of non-verbal communication of users participating in virtual environment-based teamwork simulations. This data can be used for the enhancement of virtual-environment-based simulations to increase the realism and effectiveness of team communication.
Keywords: Virtual environment; Non-verbal communication; Image processing; Training